\(\left(\frac{25}{12}\right)^5.\left(0,48\right)^4\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\frac{12}{25}\right)^x=\left(\frac{5}{3}\right)^{-2}-\left(-\frac{3}{5}\right)^4\)
\(\left(\frac{12}{25}\right)^x=\frac{144}{625}\)
\(\left(\frac{12}{25}\right)^x=\left(\frac{12}{25}\right)^2\)
\(x=2\)
Chúc bạn học tốt ^^
\(\frac{\left(\frac{2}{3}\right)^3.\left(\frac{-3}{4}\right)^2.\left(-1\right)^{2019}}{\left(\frac{2}{5}\right)^2.\left(\frac{-5}{12}\right)^3}:\sqrt{\frac{9}{25}}\)\(=\frac{\frac{2^3}{3^3}.\frac{-3^2}{4^2}.\left(-1\right)}{\frac{2^2}{5^2}.\frac{-5^3}{12^3}}:\frac{3}{5}\)
\(=\frac{\frac{2^3}{5^3}.\frac{-3^2}{2^4}.\left(-1\right)}{\frac{2^2}{5^2}.\frac{-5^3}{2^6.3^3}}:\frac{3}{5}=\frac{\frac{-1}{3.2}}{\frac{-5}{2^4.3^3}}:\frac{3}{5}\)\(=\frac{-1}{3.2}.\frac{-2^4.3^3}{5}.\frac{5}{3}\)
\(=\frac{2^3.3^2}{5}.\frac{5}{3}=24\)
\(M=\left(\dfrac{1}{3}\right)^{12}\cdot\left(\dfrac{1}{3}\right)^{-15}+\left(\dfrac{2}{5}\right)^{-4}\cdot5^{-4}\cdot32\)
\(=\left(\dfrac{1}{3}\right)^{-3}+2^{-4}\cdot32\)
\(=27+\dfrac{32}{16}=27+2=29\)
\(\left(\frac{25}{12}\right)^5.\left(0,48\right)^4\)
\(=\frac{25^5}{12^5}.\left(\frac{12}{25}\right)^4\)
\(=\frac{25^5}{12^5}.\frac{12^4}{25^4}\)
\(=\frac{25^5.12^4}{12^5.25^4}\)
\(=\frac{25}{12}\)